Difference in Motives and Basic Health Behavior of 8799 Children and Adolescents Aged 10–19 Years Following a Vegan, Vegetarian, or Omnivorous Diet - Katharina C Wirnitzer; Derrick R Tanous; Clemens Drenowatz; Gerold Wirnitzer; Manuel Schätzer; Gerhard Ruedl; Werner Kirschner (Current Developments in Nutrition, 2025)
Background: Young generations appear to be pushing for more sustainable food production as part of the trend toward healthier dietary habits. Long-term sustainable healthy behavior from secondary school ages may contribute to the life course prevention of chronic, noncommunicable diseases. Objectives: The present study aimed to analyze the motivations and key health behaviors of secondary school pupils following vegan, vegetarian, and omnivorous diets. Methods: The present study was conducted cross-sectionally with a multi-level, cluster sampling strategy. Secondary school pupils (levels I and II) in Austria were requested to complete an online questionnaire independently or with parent/guardian or teacher supervision, including questions on personal characteristics, physical activity levels, nutrition habits, dietary motives, and alcohol and nicotine habits. The statistical analysis was performed with χ2 and analysis of variance tests. Results: A total of 8799 pupils (3249 boys; 5550 girls) with an mean age of 15.1 ± 2.3 y were classified into the vegan (1.6%), vegetarian (5.6%), or omnivorous diet (92.8%). Boys were found to be more likely to follow an omnivorous diet (97%; P < 0.01). Health was the leading motivation for dietary adherence across the total sample (33.6%; 2959). Sports performance was a leading dietary motivation among the vegan diet subgroup (20.1%). Pupils following a vegan diet were the most active during leisure time (86.6%; P < 0.01) and the most consistently active across the week (3.4 ± 1.2 d/wk; P < 0.01), and the prevalence of daily fruit and vegetable intake was the highest between the vegan subgroup (81.7% and 80.3%; P < 0.01) followed by the vegetarian subgroup (72.4% and 84.2%). Conclusions: This is the first investigation to examine the differences in motives and basic health behavior between vegan, vegetarian, and omnivorous diets in school pupils. The findings indicate that following a vegan diet during childhood and adolescence is associated with more advantageous basic health behavioral choices.